Neuroimmune-Glia Interactions in the Sensory Ganglia Account for the Development of Acute Herpetic Neuralgia - Silva, Jaqueline R; Lopes, Alexandre H; Talbot, Jhimmy; Cecilio, Nerry T; Rossato, Mateus F; Silva, Rangel L; Souza, Guilherme R; Silva, Cassia R; Lucas, Guilherme; Fonseca, Benedito A; Arruda, Eurico; Alves-Filho, Jose C; et al. (The Journal of neuroscience, 2017)
Herpetic neuralgia is the most important symptom of herpes zoster disease, which is caused by Nevertheless, the pathophysiological mechanisms involved in herpetic neuralgia are not totally elucidated. Here, we examined the neuroimmune interactions at the sensory ganglia that account for the genesis of herpetic neuralgia using a murine model of Herpes Simplex Virus Type-1 (HSV-1) infection. The cutaneous HSV-1 infection of mice results in the development of a zosteriform-like skin lesion followed by a time-dependent increase in pain-like responses (mechanical allodynia). Leukocytes composed mainly of macrophages and neutrophils infiltrate infected DRGs and account for the development of herpetic neuralgia. Infiltrating leukocytes are responsible for driving the production of TNF, which in turn mediates the development of herpetic neuralgia through downregulation of the inwardly rectifying K channel Kir4.1 in satellite glial cells. These results revealed that neuroimmune-glia interactions at the sensory ganglia play a critical role in the genesis of herpetic neuralgia. In conclusion, the present study elucidates novel mechanisms involved in the genesis of acute herpetic pain and open new avenues for its control. Acute herpetic neuralgia is the most important symptom of herpes zoster disease and it is very difficult to treat. Using a model of peripheral infection of mice with HSV-1, we have characterized for the first time the neuroimmune-glia interactions in the sensory ganglia that account for the development of acute herpetic neuralgia. Among these mechanisms, leukocytes composed mainly of macrophages and neutrophils infiltrate infected sensory ganglia and are responsible for driving the production of TNF. TNF, via TNFR1, mediates herpetic neuralgia development through downregulation of the inwardly rectifying K channel Kir4.1 in satellite glial cells. This study elucidates novel mechanisms involved in the genesis of acute herpetic neuralgia and open new avenues for its control.